PENGARUH GAYA KEPEMIMPINAN, KOMITMEN ORGANISASI, DAN PEMAHAMAN SISTEM INFORMASI AKUNTANSI PADA KINERJA AUDITOR KANTOR AKUNTAN PUBLIK - Setiyadi, I Nyoman; Rasmini, Ni Ketut (E-Jurnal Akuntansi; Vol 17 No 3 (2016), 2016)
This research aimed to examine the effect of leadership styles, organizational commitment and understanding of accounting information systems auditor performance public accounting firm in the province of Bali. The theory used in this research is the theory of the Agency (Agency Theory). The population in this study were all auditors working in the office of the Public Accountant in the Province of Bali. The samples used were 54 respondents to the sampling technique used purposive sampling. Collecting data using by questionnaires. The data analysis technique used in this research is multiple linear regression. The results showed leadership styles, organizational commitment and understanding of accounting information systems auditor's of a positive effect on the performance of public accounting firm in the province of Bali.
Keywords: leadership styles, organizational commitment, understanding of accounting information systems, performance auditor